Face Recognition Using Stationary wavelet transform and Neural Network with Support Vector Machine - Alsalam Ali, Nashwan (Iraqi Journal of Science, 2023)
Face recognition is a type of biometric software application that can identify a specificindividual in a digital image by analyzing and comparing patterns. It is the process ofidentifying an individual using their facial features and expressions.In this paper we proposed a face recognition system using Stationary Wavelet Transform(SWT) with Neural Network, the SWT are applied into five levels for feature facialextraction with probabilistic Neural Network (PNN) , the system produced good resultsand then we improved the system by using two manner in Neural Network (PNN) andSupport Vector Machine(SVM) so we find that the system performance is more betterafter using SVM where the result shows the performance of the system is better based onthe recognition rate measurement.